PHYTOCHEMICAL PROFILES, ANTIOXIDANT, AND ANTICANCER ACTIVITIES FROM LEAVES AND SEEDS EXTRACT OF Myristica fragrans - Saputri, Ariyanti; Fajriah, Sofa; Cahyana, Antonius Herry; Putria, Devi Kasih; Saputra, Ziyan; Angelina, Marissa (Universitas Airlangga, Campus C Mulyorejo, Surabaya, Indonesia, 2024)
Nutmeg (Myristica fragrans) is a plant that grows naturally in Indonesia and widely used in the food and industrial sectors. Nutmeg seeds have been widely studied because they have a variety of compounds with good activities, but research on the leaves still needs to be completed. Therefore, this research compared nutmeg leaves and seed extracts' secondary metabolite content and bioactivity. This study aims to determine the phytochemical contents of nutmeg leaves and seed extracts by phytochemical screening and GC-MS analysis, as well as its potential as an antioxidant and anticancer. The antioxidant activity test uses the DPPH (1,1-diphenyl-2-picrylhydrazyl) method measured at a wavelength of 517 nm. Meanwhile, the anticancer activity test uses MCF-7 cells with the MTT assay method. Nine compounds (lipid, phenylpropanoid, lignan, terpenoid, and quinone groups) were identified by GC-MS analysis in the leaf extracts. Meanwhile, seed extract has 23 compounds from the lipid, fatty acid, phenylpropanoid, lignan, and terpenoid groups. The antioxidant activity of nutmeg leaves and seed extracts was carried out using the DPPH method, while the cytotoxic activity against MCF-7 cells used the MTT method. Nutmeg leaves have more potent antioxidant activity than nutmeg seeds, with IC50 values of 17.80 µg/mL and 53.01 µg/mL, respectively. The cytotoxic activity test on MCF-7 cells also showed that the inhibition value of nutmeg extract (26%) was higher than that of nutmeg seeds (22.73%). This research shows that nutmeg leaf extract has the potential to carry out further research regarding the bioactivity of its compounds.